Unilateral cleft lip and palate patients present cranial base modifications: a cross-sectional study - Eduardo Murad VILLORIA; Bernardo Quiroga SOUKI; Marina Araújo Leite ASSIS; Dauro Douglas OLIVEIRA; Thaís de Lima AZEREDO; Rodrigo Villamarim SOARES (Brazilian Oral Research)
Abstract The aim of this cross-sectional study was to perform a three-dimensional (3D) assessment of the cranial base of patients with unilateral cleft lip and palate (UCLP). Cone-beam computed tomography (CBCT) scans of 52 UCLP patients (21 females and 31 males; mean age, 10.0 ± 2.12 years) were compared with the scans of 72 individuals (24 females and 48 males; mean age, 11.0 ± 2.11 years) without CLP, matched by gender and age (control group, CG). The 3D Euclidean distances of anterior cranial base (N-S), posterior cranial base (S-Ba), total cranial base (N-Ba) lengths, cranial base width (Po-Po), as well as the cranial base flexure (NSBa), were measured using open-source software ITK-SNAP and 3D Slicer. Statistical analyses were carried out with the Student’s t-test at a significance level of 5%. UCLP demonstrated shorter 3D distances than CG in the N-S, S-Ba, and N-Ba cranial base lengths (p < 0.001). In comparison with female CG, female UCLP had a smaller cranial base flexure (NSBa; p = 0.020). No statistically significant differences between UCLP and CG were found for the cranial base width (Po-Po). UCLP patients presented distinct morphological cranial base characteristics in comparison with CG. These results indicate that morphological and positioning changes in the maxillary bones are not solely attributable to the cleft and/or surgical procedures.